Optimization of SPME for determination of nitro compounds using GC-MS - Eisner, Aleš; Surmová, Silvie; Kučerová, Renata; Bajerová, Petra; Bajer, Tomáš; Ventura, Karel; Adam, Martin (Univerzita Pardubice, 2017)
SPME is extraction technique, which is compatible with gas chromatography. The sensitivity may be good for determination of very low concentration levels. In this paper is this method used for determination of aromatic nitro compounds. Mixtures of aromatic nitro compounds and concentrated nitric acid are potentially useful as improvised explosive devices. Therefore, it is necessary to find sensitive analytical procedures for the determination of residues after the explosion. Connection gas chromatography with mass detector was used for analysis. It is necessary to optimize conditions SPME (time, temperature, sorption and any amount of NaCl). To optimize the use of statistical techniques DEO. Suitable extraction conditions were found with this method. These conditions were tested on real samples after the explosion.
Optimalizace SPME pro stanovení nitrosloučenin pomocí GC-MS
Keywords: SPME; GC-MS; aromatic nitro compounds; SPME; GC-MS; aromatické nitrosloučeniny